Role of the local stress systems on microstructural inhomogeneity during semisolid injection. (1st August 2021) - Bhagavath, S.; Gong, Z.; Wigger, T.; Shah, S.; Ghaffari, B.; Li, M.; Marathe, S.; Lee, P.D.; Karagadde, S.
Abstract: High pressure metal die casting is an extremely dynamic process with widely ranging cooling rates and intensifying pressures, resulting in a wide range of solid fractions and deformation rates simultaneously existing in the same casting. These process parameters and their complex interplay dictate the formation of microstructural solidification defects. In this study, fast synchrotron X-ray imaging experiments simulating high pressure die casting of aluminium alloys were conducted to investigate the effect of solid fraction, loading conditions and semisolid flow on local microstructural inhomogeneity. While most of the existing literature in this field reports speeds up to 10 µm/s for in situ deformation, the present work captures much faster filling and solidification, at speeds closer to 100 µm/s and at different solid fractions. Semisolid deformation of low solid fractions reveals two typical microstructural features: (i) coarser grains in the middle and finer ones near the walls, and (ii) remelting near the solid-liquid interface due to Cu enrichment in the liquid by the flow. Ex situ scans and digital image correlation analysis of the higher solid fraction samples reveal a porosity formation mechanism based on the local state of stresses, microstructure and feeding. Four different characteristics were identified: (i) plug flow, (ii) dead zone (densified mush), (iii) shear and (iv) bulk zones. These insights will be used to develop zone-specific strategies for the numerical modelling of defect formation during die casting. Graphical abstract: Image, graphical abstract